2021
DOI: 10.13057/biodiv/d220863
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of indigenous Arbuscular Mycorrhizal Fungi (AMF) of forest clove rhizosphere from Maluku, Indonesia

Abstract: Abstract. Mahulette AS, Alfian A, Kilkoda KA, Lawalata IJ, Marasabessy DA, Tanasale VL, Makaruku MH. 2021. Isolation and identification of indigenous Arbuscular Mycorrhizal Fungi (AMF) of forest clove rhizosphere from Maluku, Indonesia. Biodiversitas 22: 3613-3619. Forest clove is classified as wild-type and endemic to the Maluku (Moluccas) Islands, Indonesia. The different condition of growing areas causes various types of Arbuscular Mycorrhizal Fungi (AMF) associated with forest clove. The study aimed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Lekberg et al (2007) reported that AM fungi from Glomeraceae species are more prevalent in soils with higher clay content. Mahulette et al (2021) also reported that soils with clay texture and pH near neutral are dominated by Glomus sp. It supports the presence of Glomus sp.…”
Section: Arbuscular Mycorrhizal Spore Distributionmentioning
confidence: 93%
“…Lekberg et al (2007) reported that AM fungi from Glomeraceae species are more prevalent in soils with higher clay content. Mahulette et al (2021) also reported that soils with clay texture and pH near neutral are dominated by Glomus sp. It supports the presence of Glomus sp.…”
Section: Arbuscular Mycorrhizal Spore Distributionmentioning
confidence: 93%
“…The number of spores after trapping will increase compared to before trapping with different plants (Zulfita et al, 2020). The trapping culture causes changes in spore type and increases spore density in soil samples from forest cloves (Mahulette et al, 2021). High spore density and arbuscular mycorrhizal spore colonization during trapping have led to increased growth and biomass of maize and sorghum host plants (Husein et al, 2022).…”
Section: Amf Colonization Of Several Host Plants Root In Tidal Swampsmentioning
confidence: 99%
“…Mycorrhiza is a form of symbiotic mutualism between fungi and the root system of higher plants. This symbiosis can increase the ability of plants to absorb nutrients, especially P, Cu, and Zn and make plants more tolerant to metal poisoning, root disease infection, drought, and other abiotic stresses by increasing root surface area and nutrient transmission (Laksono et al, 2013;Mahulette et al, 2021). AMF can also increase plant growth on soils with low fertility levels or on degraded land and help root function in nutrient absorption (Parihar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%